Molecular characterization of Blastocystis subtypes isolated in the city of Uberaba, Minas Gerais State, Brazil - Cabrine-Santos,Marlene (2021)
Abstract INTRODUCTION Blastocystis is an intestinal protozoan that may play a role in the pathogenicity of humans. This study aimed to (i) genetically characterize Blastocystis isolates obtained from human fecal samples and the water supply of the city of Uberaba, Minas Gerais, Brazil, and (ii) to verify the phylogenetic relationship between these isolates. METHODS Blastocystis species present in 26 fecal samples obtained from humans and animals from Uberaba were genetically characterized by polymerase chain reaction-restriction fragment length polymorphism and polymerase chain reaction-sequence-tagged sites. All amplicons were partially sequenced and/or defined according to the GenBank classification. RESULTS Polymerase chain reaction amplicons were generated from 21 human isolates and 18 water samples. The subtypes defined were ST1 (53.3%), ST3 (40.0%), and ST2 (6.7%) for human isolates; ST10 (100%) for bovine isolates; and ST5 (50.0%), ST1 (25%), and ST3 (25%) for pigs. Sequencing of polymerase chain reaction products showed a 98%-99% identity for the Blastocystis sequences deposited in GenBank, except for sequences from water samples that showed the identity of algae sequences. Phylogenetic analysis of Blastocystis sequences showed two distinct groups, one of which was principally formed by ST1, ST5, and ST10, and the other by isolates characterized as ST3 and ST7. Both clades showed human and animal sequences, reinforcing the notion that Blastocystis subtypes are not host-specific. CONCLUSIONS The data showed that Blastocystis subtypes circulating in Uberaba are ST1-ST3, ST5, and ST10, present in both humans and animals, demonstrating that the Blastocystis subtypes are not host-specific; that is, zoonotic transmission is possible.